Sustainable E-Government as an Effort to Improve Indonesia's Global Competitiveness - Renti R. Budiman; Teguh Kurniawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Worldwide Governance Indicators (WGI) The World Bank has stated that one of the supporting factors for governance to increase the competitiveness of a country is quality public services that can provide multidimensional benefits to stakeholders. Sustainable e-Government is the innovation and use of ICT by the government to promote and provide better-integrated services, not limited to short service life, and flexible to changes and needs. This article aims to explain how efforts are made to achieve sustainable e-Government. The research method used is a qualitative method through literature study. The results of the study explain that achieving sustainable e-Government includes at least five critical dimensions which consist of legal support, simplification of bureaucracy or institutions; institutional and regulatory framework, organizational set-up and culture, a comprehensive technology infrastructure through e-government architecture Enterprise Architecture (EA), literacy skills of ICT of human resources, and cross-organizational collaboration.